Capim-elefante ensilado com diferentes níveis de farelo úmido de glúten de milho (FUGM): aspectos nutricionais, comportamento ingestivo e digestibilidade aparente em ovinos - Gonçalves, Mayara Fabiane (2014)
Wet Corn Gluten Feed (WCGF) is a byproduct of milling corn syrup and starch manufacturing this grain . This coproduct can be ensiled forages standard in an attempt to improve their conservation . The objective of this study was to evaluate the nutritional value of silage of elephant with inclusion of four different levels of wet corn gluten Feed (WCGF) , the behavior of sheep fed with these silages and consumption and digestibility of these foods . No significant differences ( p < 0.05 ) for the temperatures of elephant grass silages with 0 , 30 and 60 % inclusion of FUGM on day 0 , only the highest level of inclusion ( 90 % ) showed higher temperature , 41 46 º C. On day 50 there was no difference ( p < 0.05 ) between any levels of inclusion in WCGF elephant grass silage . Silages of elephant grass WCGF + , the pH values decreased linearly on day 0 and increased linearly after 50 days of fermentation. The content of the silage of elephant grass on day 0 was increased quadratically as increased inclusion of WCGF since the day 50 post -fermentation all treatments showed higher MS compared to day 0. IVDMD of elephant grass silage was higher in levels 0 and 30 % inclusion after 50 days of fermentation, whereas there were no significant differences ( p > 0.05) with corn silage inclusion FUGM . Physical characteristics of silages did not change much with the inclusion levels . In relation to feeding behavior can be observed that the best ERMS found in treatments with 60 and 90 % of inclusion WCGF. The particle size increased linearly in sizes ranging from 19mm to 8mm (Y = 21.16 +0.28 X) the inclusion of higher FUGM coproduct . Have food particles with a size between 8 mm and 1.18 mm were found in greater amounts in treatments with 30 % and 60 % inclusion of WCGF, T30 and T60 respectively , with ascending quadratic regression . The FDNfe linearly regressed ( Y = X 33.91-0.16 ) with the inclusion of coproduct WCGF. The ruminal pH of animals fed diets varied between 6.44 and 6.90 . The treatments with higher inclusion levels FUGM , T60 and T90 , showed lower pH values . For consumption and digestibility , it was found that there was no significant difference ( p > 0.05) for dry matter intake (DMI ) in g / day compared to bodyweight ( DMILW ) and in relation to metabolic weight ( CMSPV0 , 75 ) . The use of neutral detergent fiber ( NDF ) and acid detergent fiber ( CFDA ) did not differ statistically ( p > 0.05 ) between treatments . The apparent digestibility of dry matter ( CDMS ) was higher when there is some level of inclusion in FUGM regarding elephant grass silage without including this coproduct .